Simulation on airflow inside the nasal cavity with and without uncinate process - Muhammad, Nor Shakiman (2010)
Functional Endoscopic Sinus Surgery (FESS) is proposed for people with chronic sinus problems who do not respond to medical therapy. During (FESS) procedure, removal of uncinectomy is necessary. Excision of the uncinate process (UP) is to open the maxillary sinus orifice. The UP is a small structure bone in nasal cavity and it's located under the middle turbinate membranes. However, some patients have claimed that the (FESS) process has reduces their smelling capabilities and voice impairment. Due to this, this study is focusing the effect of changes airflow pattern after remove the UP. The main objective of this study is to simulate, compare and analyze the flow properties inside the nasal cavity with and without UP. This simulation has been done with 3 different models of nasal cavity. The parameter for this simulation is 0.0075m3s-1 and 0.015m3s air flow rate at the inlet nostril and ambient pressure at the outlet throat. These simulation show positive result and this indicates that the removal of the UP will result smelling capabilities decrease and voice impairment.